A new comparative testing method for equestrian helmets. Issue 3 (4th May 2022) - Bourdet, Nicolas; Deck, Caroline; Meyer, Frank; Willinger, Rémy
Abstract: The helmet is the only head protection element for jockey in the falling situation. To date, the standard test for shock absorption capacity of the equestrian helmet consists of only linear impacts and uses outdated injury criteria. Previous studies have shown the existence of normal and tangential components of the impact velocity. The present study presents a new method for the evaluation of equestrian helmet against moderate brain injury coupling experimental tests and numerical simulations. The experimental tests consist in helmeted and instrumented hybrid III dummy head impacting a rigid anvil under linear and oblique impact configurations. These impact conditions allow to highlight the protective effect of the helmet under tangential impact by using an advanced finite element head model and make it possible to estimate the level of brain injury risk by computing the brain shear stress. The method was applied to a set of 7 equestrian helmet models leading to a total of 86 experimental impact tests and 86 numerical simulations of brain response. It was observed that the moderate risk of commotion was ranged from 20% to 90%. It is shown that the most critical impacts are the linear-lateral configuration as well as the oblique impact leading to rotation around the vertical axis, leading to around 85% and 65%, respectively, risks of moderate neurological injuries. Based on this new test method, the study allows us to compare the protective capability of a given equestrian helmet and possibly compare equestrian helmets via a dedicated rating system.